PELATIHAN PENGGUNAAN INTERNET DAN SOSIAL MEDIA UNTUK MENINGKATKAN KEGIATAN PRODUKTIF BAGI MASYARAKAT - Pualam Dipa Nusantara (FT-USNI, 2024)
The use of Internet technology has become a human need. Social media, which is one of the Internet services, is an important application that needs to be studied and utilized for economic activities by the general public. Of the various purposes of the website, many are applications that are beneficial to the community, especially for the Alamanda Mix community, namely the UMKM community fostered by Bina Nusantara University in the Kemanggisan area, West Jakarta. To improve understanding of social media and its use, training is needed for the community, especially those who want to use social media in their daily lives, especially to support economic activities. The purpose of the training as part of community service is to provide knowledge on how to use social media which is expected to increase community productivity. Of the 18 training participants, all stated that this training brought positive benefits and could be applied to everyday life.